Syntactical Analysis in Jkt48’s Flying High Song Lyrics - Mubarok, Moch. Kavil; Hikmah, Durratul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study examines the syntactic structure found in the lyrics of the song Flying High by JKT48 using Nelson Francis’s sentence classification theory. This study also analyzes the functional meaning in song lyrics through Halliday’s Systemic Functional Linguistics (SFL) approach. The purpose of this study is to identify the syntactic structure contained in song lyrics and how the meaning of song lyrics is conveyed functionally. This study employs a qualitative descriptive method with a text analysis approach. Data was collected through official lyrics documentation and analyzed based on syntactic structure and functional grammar elements, including three metafunctions: ideational, interpersonal, and textual. The results show that the most dominant sentence structure in the lyrics is the Structure of Predication + Complementation + Modification, reflecting clarity of meaning and alignment with the musical rhythm. Functionally, the lyrics are dominated by material processes (ideational), declarative forms with strong modality (interpersonal), and personal themes (textual) that emphasize spirit, emotion, and personal perspective. This study shows that song lyrics, despite their apparent simplicity, hold significant value for both syntactic and functional analysis. The integration of form and function in the lyrics reveals the depth of meaning that supports the motivational theme of the song.